2015
DOI: 10.3390/diagnostics5040546
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Diffusion-Weighted Imaging (DWI) in Locoregional Therapy Outcome Prediction and Response Assessment for Hepatocellular Carcinoma (HCC): The New Era of Functional Imaging Biomarkers

Abstract: Reliable response criteria are critical for the evaluation of therapeutic response in hepatocellular carcinoma (HCC). Current response assessment is mainly based on: (1) changes in size, which is at times unreliable and lag behind the result of therapy; and (2) contrast enhancement, which can be difficult to quantify in the presence of benign post-procedural changes and in tumors presenting with a heterogeneous pattern of enhancement. Given these challenges, functional magnetic resonance imaging (MRI) techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 62 publications
2
17
1
Order By: Relevance
“…While low ADC was found to correlate with poorer outcomes in this study, this observation has not been seen consistently in previously published reports [ 12 ]. Multiple studies have investigated the evaluation of pre-treatment ADC values to accurately predict response to chemoembolization with varying results [ 13 , 14 , 15 , 16 ].…”
Section: Discussioncontrasting
confidence: 54%
“…While low ADC was found to correlate with poorer outcomes in this study, this observation has not been seen consistently in previously published reports [ 12 ]. Multiple studies have investigated the evaluation of pre-treatment ADC values to accurately predict response to chemoembolization with varying results [ 13 , 14 , 15 , 16 ].…”
Section: Discussioncontrasting
confidence: 54%
“…We could not correlate MRI findings with histopathological changes as performing repeat biopsies solely for the purposes of research is not ethical. We did not examine DWI sequence data and ADC values, which have been proven a reliable for the diagnosis of pulmonary nodules [ 2 , 27 ], and evaluation of therapeutic response [ 21 , 28 ]. These examinations were not performed because there were artifacts on DWI images at 1 day and 1 week post-cryoablation, and putting the ROI in the correct place was difficult due to cavity formation.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic contrast-enhanced (DCE)-MRI and its volume transfer coefficient (K trans ) have been demonstrated to correlate with MVD, and may quantitatively reflect tumor angiogenesis ( 5 , 14 ). Furthermore, studies have demonstrated that diffusion-weighted imaging (DWI) and the apparent diffusion coefficient (ADC) are useful in evaluating cellularity and monitoring the tumor response to therapy ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%